Bellendenker gen. nov., a new Australian genus of Glandulariini (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2017)
Bellendenker palpalis gen. et sp. nov. is described based on specimens collected in northeastern Australia. The genus is unique among glandulariine Scydmaeninae in strikingly elongated labial palps, which are longer than the labium; no modifications of labial palps have been known so far in this large tribe. Bellendenker is most similar to the Australian genus Scydmaenozila Jałoszyński, they share similar thoracic structures. Numerous differences in cephalic characters can be used to distinguish these genera; moreover, adults of Bellendenker are wingless and have reduced structures of the elytral base. Fourteen genera of Glandulariini (plus one of unclear status, known only from original description) are currently known to occur in Australia, eight being endemic to this continent.